Handbook of research on reading comprehension - Israel, Susan E. (The Guilford Press, 2017)
"This edition provides a transformative snapshot of reading comprehension as a field of study at a seminal moment. It maintains the same high level of standards with respect to (1) historical perspectives useful for laying the foundation of study on reading comprehension; (2) theoretical perspectives that allow the reader to consider different views on how specific areas have evolved since the first edition; (3) excellent chapters on various elements of reading comprehension, including major research studies in assessment, cultural impacts of reading comprehension, issues affecting English language learners, and consideration of international populations; and (4) identification of future research needs to help raise important questions and stimulate possible hypotheses for future research"--Provided by publisher.